Digital Transformation and the Environment: An Analysis of the Impact of Digital Transactions on Carbon Emissions in Indonesia - Pukuh, Nugraha; Widyasthika, Hayu Fadlun; Hakim, Shinta Mahaputri (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2025)
The rapid rise in carbon emissions due to economic expansion has accelerated global warming and climate change. Amid these challenges, digital transformation in retail and financial services has emerged as a potential solution to mitigate environmental degradation. This study analyzes the impact of digital transactions—online shopping and financial technology—on carbon monoxide emissions in Indonesia using panel data from 34provinces between 2019 and 2022. Employing a fixed effects panel regression model, the analysis reveals that higher adoption of digital transactions significantly reduces carbon monoxide levels. The number of vehicles is positively associated with emissions, while tertiary education levels contribute to emission reduction. These findings suggest that promoting digital finance and e-commerce can support the transition toward a low-carbon economy. This study offers empirical evidence for policymakers to integrate digital transformation into environmental strategies